The Identification and Analysis of the Self-Incompatibility Pollen Determinant Factor SLF in Lycium barbarum - Jiali Wu; Xiongxiong Nan; Xin Zhang; Wendi Xu; Haijun Ma; Zijun Yang; Cuiping Wang (Plants, 2024)
Self-incompatibility is a widespread genetic mechanism found in flowering plants. It plays a crucial role in preventing inbreeding and promoting outcrossing. The genes that control self-incompatibility in plants are typically determined by the S-locus female determinant factor and the S-locus male determinant factor. In the Solanaceae family, the male determinant factor is often the SLF gene. In this research, we cloned and analyzed 13 S2-LbSLF genes from the L. barbarum genome, which are located on chromosome 2 and close to the physical location of the S-locus female determinant factor S-RNase, covering a region of approximately 90.4 Mb. The amino acid sequence identity of the 13 S2-LbSLFs is 58.46%, and they all possess relatively conserved motifs and typical F-box domains, without introns. A co-linearity analysis revealed that there are no tandemly repeated genes in the S2-LbSLF genes, and that there are two pairs of co-linear genes between S2-LbSLF and the tomato, which also belongs to the Solanaceae family. A phylogenetic analysis indicates that the S2-LbSLF members can be divided into six groups, and it was found that the 13 S2-LbSLFs are clustered with the SLF genes of tobacco and Petunia inflata to varying degrees, potentially serving as pollen determinant factors regulating self-incompatibility in L. barbarum. The results for the gene expression patterns suggest that S2-LbSLF is only expressed in pollen tissue. The results of the yeast two-hybrid assay showed that the C-terminal region of S2-LbSLFs lacking the F-box domain can interact with S-RNase. This study provides theoretical data for further investigation into the functions of S2-LbSLF members, particularly for the identification of pollen determinant factors regulating self-incompatibility in L. barbarum.